Dynamics of stand productivity in Moso bamboo forest after strip cutting - Zheng, Yaxiong; Fan, Shaohui; Zhou, Xiao; Zhang, Xuan; Guan, Fengying (Frontiers in Plant Science, 2022)
Strip cutting can effectively reduce the cutting cost of bamboo forests and promote the transformation and upgradation of bamboo forests through mechanization and modernization. Despite the rapid accumulation of Moso bamboo biomass, the dynamics of five years changes in stand characteristics and productivity after cutting remain unclear. This is critical for formulating efficient bamboo forest management measures. In this paper, plots with an 8 m width strip cut (SC) and respective reserved belts (RB) were selected as the research object, and the traditional management forest (CK) as control. The dynamic characteristics of stand, biomass distribution pattern, and productivity change in the different treatment plots were studied for 5 years after cutting. The results showed that cutting increased the number of shoots and new bamboo, and decreased the diameter at breast height, height to crown base, and height of new bamboo (p<0.05). Cutting reduces the productivity of both SC and RB, and allocates more biomass to the bamboo leaves to capture light in SC (p<0.05). Over time, the characteristics of new bamboo in SC reached the level of CK, and the density of standing bamboo, and productivity, were higher than those in CK. However, the number and productivity of new bamboo decreased significantly in the RB (p<0.05), which reflected the density restriction effect of bamboo forest. Further analysis showed that the increase in productivity in SC and CK was mainly from Moso bamboo at II and III “du”, which positively correlated with the soil contents of total nitrogen, total phosphorus, and available phosphorus. It was suggested that after three On-year restorations, the SC could reach the level of CK, however it is necessary to density manage RB from the second On-year after cutting.